2007
DOI: 10.1073/pnas.0702196104
|View full text |Cite
|
Sign up to set email alerts
|

Fossil genes and microbes in the oldest ice on Earth

Abstract: Although the vast majority of ice that formed on the Antarctic continent over the past 34 million years has been lost to the oceans, pockets of ancient ice persist in the Dry Valleys of the Transantarctic Mountains. Here we report on the potential metabolic activity of microbes and the state of community DNA in ice derived from Mullins and upper Beacon Valleys. The minimum age of the former is 100 ka, whereas that of the latter is Ϸ8 Ma, making it the oldest known ice on Earth. In both samples, radiolabeled su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
80
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(84 citation statements)
references
References 32 publications
2
80
0
2
Order By: Relevance
“…Nevertheless, the models reported to date suggest the interstellar transfer of oxygenic photosynthesis, let alone any organisms, to be a very low probability event. In addition, the integrated exposure to cosmic radiation over such long durations of time will likely be sterilizing, at least extrapolating evidence on the viability of terrestrial microorganisms preserved in ice (Bidle et al 2007). …”
Section: Interstellar Transfermentioning
confidence: 97%
“…Nevertheless, the models reported to date suggest the interstellar transfer of oxygenic photosynthesis, let alone any organisms, to be a very low probability event. In addition, the integrated exposure to cosmic radiation over such long durations of time will likely be sterilizing, at least extrapolating evidence on the viability of terrestrial microorganisms preserved in ice (Bidle et al 2007). …”
Section: Interstellar Transfermentioning
confidence: 97%
“…Hodson et al (22) reported the presence of inorganic and organic forms of nitrogen and phosphorus for two glaciers in Arctic Svalbard. These authors proposed the occurrence of NH 4 ϩ assimilation and nitrification on the glacier surface and denitrification and sulfate reduction in subglacial environments. In the present study, no evidence for nitrification or respiratory sulfate reduction was detected, but dissimilatory and assimilatory nitrate/ nitrite reduction was found.…”
Section: Vol 75 2009mentioning
confidence: 99%
“…To date, a pyrosequencing-based metagenomic analysis of a permanently frozen habitat has not been conducted. In several studies, the prokaryotic diversity of glacial and subglacial habitats in America (9,44), Asia (10,55), Antarctica (4,37), Greenland (32,42), and New Zealand (19) has been analyzed based on cultivation and analysis of 16S rRNA genes. However, studies of the microbial composition of European glaciers are rare.…”
mentioning
confidence: 99%
“…Genomic DNA and viable bacteria are preserved in ancient ice and permafrost for hundreds of thousands to millions of years (4)(5)(6)(7)(8). The presence of a solute-rich liquid phase within the ice matrix has been argued to be a habitat suitable for microorganisms (9)(10)(11).…”
mentioning
confidence: 99%